Realigning Distribution Strategies for Effective Marketing Operations of a Business:An Empirical Study Based on Tropicana - Dawn, Suman Kumar (Indian Journal of Marketing, 2011)
The role of distribution functions in marketing management has been gaining popularity over the years. In a dynamic marketplace of the 21st century, customers are becoming more and more demanding. They are much more informed than ever before. They are aware of their options and are willing to exercise their options. Companies have to put more efforts to gain and retain customers in a marketplace, which is specially characterised by ever growing competition. The end customer's influence on distribution channel is constantly growing and all business organisations involved in the distribution channel have to accept this challenge and come up with strategies which will be agile and responsive to changes in customer expectations. The manufactures, distributors, channel partners and retailers can no more decide the way they want to sell. It is the end customers who dictate what and how they want to buy. At the same time, competition is growing. Geographical boundaries are no more a constraint in a marketplace. So there is a need to adjust and reengineer the distribution channels and strategies to meet the end customers' requirements. In designing and developing an effective distribution channel network, a producer must consider product characteristics, customer characteristics, middlemen characteristics, competitor characteristics and environmental characteristics. This study involves an in-depth market survey on distribution effectiveness of Tropicana product of PepsiCo. The present study also involves on analysing the market condition of Tropicana product and also the consumer perception of the same. After analysing the market of juice segment, a suitable distribution model and strategies can be drawn.